2022
DOI: 10.1002/solr.202200362
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled 2D/2D Schottky Heterojunction of Ti3C2/UiO‐66 Nanosheets for Boosting Photocatalytic H2 Evolution

Abstract: The construction of heterojunctions is usually considered as a common strategy to improve charge separation and transfer during the photocatalytic hydrogen evolution reaction (HER) process. Originating from the surficial electrical characteristic of Ti3C2 nanosheets and 2D UiO‐66, a novel 2D/2D Ti3C2/UiO‐66 composite is facilely constructed by the electrostatic self‐assembly process for HER. Higher photocatalytic HER efficiency (265.2 μmol h−1 g−1) is achieved for 2D/2D composites compared to both, pristine 3D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…This suggested that there is a strong coupling effect at the interface between GDY and PMF. [ 23 ] Figure 2b shows the XRD test results of GDY. As shown in Figure 2b, the characteristic peak of GDY appears at 22°, which corresponds to the (002) crystal plane of the amorphous carbon material.…”
Section: Resultsmentioning
confidence: 99%
“…This suggested that there is a strong coupling effect at the interface between GDY and PMF. [ 23 ] Figure 2b shows the XRD test results of GDY. As shown in Figure 2b, the characteristic peak of GDY appears at 22°, which corresponds to the (002) crystal plane of the amorphous carbon material.…”
Section: Resultsmentioning
confidence: 99%
“…[42] For Ti 3 C 2 , the formation of Schottky with other semiconductor materials and the generation of an internal electric field can improve carrier separation, effectively improving the photocatalytic efficiency. [43,44] Due to its good structural stability, hydrophilicity, metal conductivity, low Fermi level and abundant active centers, as a new and cheap non-noble metal cocatalyst, it has been widely used in CO2 photoreduction. [45] Therefore, TI 3 C 2 was chosen as the cocatalyst of g-C 3 N 4 /MoSe 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] One of the main challenges is how to ensure efficient charge separation to achieve active sites for photocatalytic hydrogen reaction evolution. So far, many strategies including reasonably designing photocatalysts via elemental doping or defect engineering, [5][6][7] introducing single-atom catalysts (SACs) [8,9] or constructing heterojunctions, [10,11] have already been proposed. mobility, while strong electron affinition could hinder the charge transfer process.…”
Section: Introductionmentioning
confidence: 99%